Absorption heat transformers: Sensitivity study to answer existing discrepancies. (January 2019) - Wakim, Michel; Rivera-Tinoco, Rodrigo
Abstract: This work aims at bringing an analysis upon the heterogeneity and the accuracy of results expressed by authors studying absorption heat transformers (AHTs). Existing work is based on specific operating conditions for specific applications, which shows that detailed thermodynamic and sensitivity studies for a wide range of operating conditions are lacking. Hence, this work shows the impact of wide ranges of operating temperature values upon exergy destruction, COP and performance variations. Main results show a maximum in performance for a given working pair as a function of temperatures and refrigerant content in the fluids at the generator, absorber and evaporator. Exergy destruction in generators and absorbers is confirmed, however, it is for the first time shown that there is a counterbalancing effect between these two components of the AHT. This effect explains why conclusions of works published on AHT seem to lead to contradictory pathways towards optimization. Highlights: There are some contradictions between the results obtained from all the previous theoretical studies made. Reasons for this discrepancies are for the first time provided. The main factor affecting the performance of the cycle is the difference in absorbent concentration of the refrigerant-absorbent solution between the generator and the absorber. To upgrade the performance of low temperature heat recovery using SAHTs, an improvement on both absorbers and generators is needed.